Growth of ornamental sunflower in pot at field level by effect of arbuscular mycorrhizal fungi - Vital-Vilchis, Isabel; Quiñones-Aguilar, Evangelina Esmeralda; Hernández-Cuevas, Laura Veronica; Rincón-Enríquez, Gabriel (REVISTA TERRA LATINOAMERICANA, 2020)
Sunflower popularity as an ornamental plant has increased dramatically in the last decade. The arbuscular mycorrhizal fungi (AMF) increased the diameter of the floral chapter and early flowering in the gerbera; however, this effect depends on the inoculum species of AMF and the host plant. The aim of this study was to assess the effect of different AMF inoculums on plant growth of different sunflower ornamental varieties. A two factors random block experiment with six replicates in Zapopan at 2017 was established; AMF with f ive levels: Rhizophagus intraradices (Ri), Funneliformis mosseae (Fm), consortium Cerro del Metate (CM), Las Campesinas (LC) and without AMF; ornamental sunflower variety with four levels: belleza de otoño (BO), gigante simple amarillo (GSA), doble enana (DE) and doble gigante (DG). Seventy days after having established the experiment, growth variables and mycorrhizal colonization percentage were measured. Results showed that GSA-CM was superior in plant growth to other treatments (Tukey, P ≤ 0.05). The consortium CM of AMF stimulated GSA growth in comparison with respect to the non-inoculated by 31%. Nevertheless, the variety BO showed 60% growth decrement whenever inoculated with AMF in comparison with the control without AMF. Fm inoculum had the lowest mycorrhizal colonization percentage (28%), despite of this, it showed signif icant effects over ornamental sunflower varieties growth. These results suggest the wide diversity of responses, in terms of growth, depending on the variety of sunflower and the type of AMF.